Geomorphology from ‘on high’: The use of drones/ UAV technology in teaching soil erosion (The Journal of Geography Education in Africa, 2022)
Unmanned Aerial Vehicles (UAV) are increasingly being utilised in scientific research endeavours and considered for field-based experiential education. UAVs are making it safer and less complex for a researcher to conduct scientific studies in a cheaper and faster manner compared to contemporary methods. In this study, a UAV was used to determine how effective the onboard camera’s resolution would compare to aerial imagery and how this can be utilised in the educational field. The UAV was flown at various heights above the ground imaging a Pixel Density Reference Chart (PDRC), to determine the most appropriate height to obtain the highest quality image. At a height of 100 m above ground level, the on-board 4k camera provides pixels, which each cover a ground area of 5 cm x 5 cm. At this height, the onboard camera covers a total ground area of approximately 30 000 m2. With the ability to monitor erosional landforms and the capability to duplicate the image position for comparing images over time, UAVs can be critical spatial tools in illustrating landform features. The UAV can be a critical tool for an educator, to assist in teaching and improving students’ knowledge of the processes behind soil erosion, image capturing, geo referencing and GIS.
Keywords: Unmanned Aerial Vehicles; Education; 3-Dimensional mapping; Gully erosion; Erosion Mapping